Effects of parenting styles and emotional intelligence on self-efficacy and self-esteem in late adolescence: Gender differences - Žukauskienė, R.; Malinauskienė, O.; Erentaitė, R. (Psichologija, 2011)
Previous studies have found that parenting styles predict childrens’ emotional intelligence, i.e., their ability to perceive, express and manage their emotions. Parenting styles were also found to predict the self-efficacy and self-esteem of adolescents. Despite a high interest in the effects of parenting on the emotional charateristics and adjustment indicators of adolescents, researchers have rarely analysed the effects of gender on these links. Previous data suggest that adolescent boys have a higher self-esteem as compared with girls, while findings on gender differences in emotional intelligence are mixed. Moreover, some effects of the interaction between parents’ and adolescents’ gender have been found significant when predicting the adjustment of adolescents. The present study explores the way in which parenting styles and adolescents’ emotional intelligence (perception and understanding of emotions, expression and labeling of emotions, and managing and regulating emotions) predict the self-esteem and self-efficacy of adolescent boys and girls. Data for this analysis were taken from a longitudinal study in high schools of the Klaipėda region. The sample consisted of 1028 adolescents (624 girls and 404 boys) aged 16 to 18 (M = 16.29, SD = 0.93). The participants filled in the Rosenberg’s Self-Esteem Scale (RSE, Rosenberg, 1965), parenting styles questionnaire (EMBU: Egna Minnen Beträffande Uppfostran, Arrindell et al., 1994), the Emotional Skills and Competence Questionnaire (ESCQ-45, Takšić et al, 2009), and the Generalized Self-efficacy Scale (GSE, Schwarzer and Jerusalem, 1995). The results revealed significant gender effects: girls scored higher on all subscales of emotional intelligence (perception and understanding, expression and labeling, and managing and regulating emotions), including the total emotional intelligence score. In line with the previous studies, self-efficacy did not differ by gender, but boys had a higher self-esteem as compared with girls. Both parents showed more emotional warmth to their daughters, while fathers (but not mothers) showed more rejection towards their sons. Of all parenting styles, parental emotional warmth had the strongest links with the emotional intelligence of adolescent girls and boys. The other links between parenting styles and adolescents’ emotional intelligence were gender-dependent in both parents and adolescents. Self-esteem and self-efficacy in adolescents were strongly predicted by their emotional intelligence scores, whereas parenting styles (father’s emotional warmth) were only important in predicting boys’ self-esteem.